Lipid analysis in Haematococcus pluvialis to assess its potential use as a biodiesel feedstock - Damiani, Maria Cecilia (2010)
The lipid content and composition of Haematococcus pluvialis exposed to stress conditions were analyzed to assess the potential of this microalga as a biodiesel feedstock. The total lipid content of control cells was 15.61% dw, whereas that of cells exposed to continuous high light intensity with nitrogen-sufficient medium (A-stress condition) or under continuous high light intensity with nitrogen-deprivation medium (B-stress condition) was 34.85% dw and 32.99% dw, respectively. The fatty acid profile was similar under all conditions and indicated that the main components were palmitic, stearic, oleic, linoleic, linolenic and linolelaidic acids. The neutral lipid fraction increased about 2-fold under both stress conditions. The percentage of saturated fatty acids in the neutral lipid fraction was 30.36% and 29.62% in cultures grown under A-stress and B-stress, respectively, and 27.81% under control conditions. The monounsaturated fatty acid content was not significantly different in control and A-stress cultures (20.07% and 19.91%, respectively), but was 18.96% under B-stress. The content of polyunsaturated fatty acids was 47.23% under B-stress and 43.15% under A-stress. Growth-rate was higher under A-stress compared to B-stress. This is the first study of H. pluvialis that provides a detailed characterization of its lipid content in relation to bioenergy. The results indicate the potential of this microalga as a biodiesel feedstock; however, culture conditions still have to be improved in order to achieve an adequate energy balance in mass culture. © 2010 Elsevier Ltd. All rights reserved.